Use of focused intensive care echo in the diagnosis of primary cardiac angiosarcoma. Issue 12 (17th September 2020) - Medhora, Jasmine; Wilson, Graham; Ronald, Andrew; Allen, Lee
Abstract: Focused Intensive Care Echo can aid diagnosis in complex patients where initial investigations are non‐diagnostic. FICE is an essential skill for critical care physicians, and bedside echocardiography should be a standard investigation for all critical care patients. Abstract : FICE can aid diagnosis in complex patients where initial investigations are non‐diagnostic. FICE is an essential skill for critical care physicians, and bedside echocardiography should be a standard investigation for all critical care patients.